Agroecosystem-based agricultural genetic resources for balanced and diversified food, nutrition, health, business, geographical indication and environment - Joshi, Bal Krishna; Shrestha, Ram Krishna; Khanal, Ram Chandra; Gauchan, Devendra (Informa UK Limited, 2024)
Nepal has 15 distinct agroecosystems spread across three major agroecozones: Tarai, Mid Hill, and High Hill. These regions support a rich variety of agrobiodiversity. This paper examines the significance of native agrobiodiversity within each of these agroecosystems for diversified food, nutrition, health, business and environment. The information presented is derived from various literature sources, discussions with key experts, and the authors' own experiences. Each of these agroecosystems has cultivated and preserved numerous unique species, landraces, and genotypes of agrobiodiversity, including crops, forages, livestock, agro-insects, agro-microorganisms, and aquatic genetic resources. This agrobiodiversity is deeply connected with local cultures, traditional knowledge, and skills. The high diversity of agricultural genetic resources (AGRs) within Nepal's relatively small area is a crucial factor for ensuring food security, nutrition, health, business opportunities, and environmental sustainability. Many niche products, prized for their purity, quality, taste, health benefits, and nutritional value, are sold at premium prices. However, the focus on production-centric agricultural programs over the years has led to the replacement of many niche-specific varieties by more uniform and limited ones. Introducing new genotypes into a particular agroecosystem may undermine the principles of ecological agriculture. Therefore, it is essential to enhance the competitiveness of native AGRs and associated indigenous technologies within each agroecosystem.